Learn Questions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# If f(x) = x^{4} − x^{3} + x^{2} and g(x) = −x^{2}, Where x ≠ 0, What is (f/g)(x)?

We will use the concept of functions to solve this.

## Answer: If f(x) = x^{4} − x^{3} + x^{2} and g(x) = −x^{2}, then (f/g)(x) = x − x^{2} − 1

Let's solve this step by step.

**Explanation:**

Given that, f(x) = x^{4} − x^{3} + x^{2} and g(x) = −x^{2}

We know from function that: (f/g)(x) = f(x) / g(x)

(f/g)(x) = (x^{4} − x^{3} + x^{2}) / (−x^{2})

= x^{2}(x^{2} − x + 1) / (−x^{2})

= -(x^{2} − x + 1)

= x − x^{2} − 1

### Hence, If f(x) = x^{4} − x^{3} + x^{2} and g(x) = −x^{2}, then (f/g)(x) = x − x^{2} − 1

Math worksheets and

visual curriculum

visual curriculum